Composite film for fruit preservation as well as preparation method and application of composite film

By using a composite membrane prepared by mixing lycopene with chitosan and polymer compounds, the problem of unsatisfactory fruit preservation technology is solved, and the effect of extending the shelf life of the fruit and maintaining quality is achieved.

CN119505376APending Publication Date: 2025-02-25JIAXING UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411663729.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing fruit preservation technology has the problem of poor results, especially for perishable fruits such as strawberries and bananas. The existing methods are difficult to effectively extend their shelf life and maintain quality.

Method used

Using a composite membrane, the preparation method includes mixing lycopene with a film-forming matrix (chitosan and polymer compounds such as corn starch or polyvinyl alcohol) to form lycopene-chitosan-corn starch or Lymph-chitosan-polyvinyl alcohol composite membrane.

Benefits of technology

This composite membrane can effectively delay the decline rate of weight loss, rot rate, titrate acid content and vitamin C content of fruits, prolong the shelf life of fruits and maintain their nutrients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505376A_ABST
    Figure CN119505376A_ABST
Patent Text Reader

Abstract

The invention relates to the field of fruits, in particular to a composite film for fruit preservation and a preparation method and application thereof. The invention provides a composite film for fruit preservation. The composite film comprises the following preparation raw materials: prodigiosin and a film forming substrate, the film-forming substrate comprises chitosan and a high-molecular compound; the high-molecular compound is corn starch or polyvinyl alcohol. Compared with a composite film without addition of prodigiosin, the composite film provided by the invention can delay the weight loss rate, the rotting rate, the titratable acid content and the vitamin C content of the fruits, can effectively retain nutrient substances of the fruits, and prolongs the storage period of the fruits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fruits, and in particular to a composite film for preserving fruits, and a preparation method and application thereof. Background Art

[0002] With the rapid development of the food industry and the increasing demand of consumers for food safety and health, the research on food preservation technology has become a hot area. Especially for perishable fruits and vegetables, such as strawberries and bananas, which have high economic value and are easily corrupted, it is particularly important to develop new and effective preservation materials and technologies. Strawberries and bananas still maintain a high metabolic rate after picking, and are easily infected by pathogens and mechanically damaged, thus seriously affecting the market value of strawberries and bananas and consumers' eating experience.

[0003] At present, the methods of fruit preservation include physical preservation, chemical preservation and biological preservation. Physical preservation includes controlled atmosphere storage, heat treatment technology and irradiation technology. Controlled atmosphere storage refers to supplementing and reducing the CO2 or O2 concentration of the storage environment or filling a certain concentration ratio of inert gas to achieve the purpose of reducing the respiration intensity of fruits and vegetables; but due to the different origins and varieties of fruits, the gas conditions required for storage are also different, which may cause the fruit to enter the anaerobic fermentation pathway, thereby deteriorating the quality of the fruit. Heat treatment is a physical method such as hot water, steam and hot air to kill eggs and larvae on the skin and inside of fruits and vegetables, reduce the softening rate of fruits and improve the storage and preservation effect; but this method will have an adverse effect on the taste and color of fruits. Irradiation technology uses high-energy rays to kill food pathogens and other spoilage bacteria, but due to its high cost and low consumer acceptance of this technology, the progress of irradiated food is limited. The chemical preservatives that are currently being studied include chlorine dioxide, hydrogen peroxide, cyclopropene, ethylene effect inhibitors, etc., but the preservation effect of these chemical preservatives is not ideal. Biological preservation technology refers to the use of microbial antagonism or the addition of antibacterial and bactericidal active substances obtained from organisms to the coating or soaking the target food in a solution to inhibit spoilage bacteria and extend the shelf life of food. However, due to the reproduction of antagonistic bacteria and their susceptibility to many factors such as the environment, the environmental conditions for its production and storage are also very strict, and there are also hidden dangers of latent pathogens, which are difficult to apply in practice.

[0004] In recent years, white pollution has seriously threatened the ecological environment and even endangered human life and health. Natural and degradable packaging materials have received more and more attention. In recent years, researchers have been committed to using edible coatings as a preservation method for fruits and vegetables instead of synthetic plastic packaging. Edible coatings are an application of edible films, which are a thin layer of polymer biomaterials formed on the surface of food by spraying or dipping, which plays a role in isolating air, thereby preventing food from spoiling, extending the shelf life and maintaining its sensory properties. However, due to its poor preservation effect, it is not currently promoted in the market. Therefore, it is necessary to explore preservation methods that can extend the shelf life of fruits and slow down quality deterioration. Summary of the invention

[0005] The purpose of the present invention is to provide a composite film for fruit preservation and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art. The composite film provided by the present invention can effectively extend the shelf life of fruits and slow down the deterioration of quality.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] The present invention provides a composite film for preserving fruits, the composite film comprising the following preparation raw materials: prodigiosin and a film-forming matrix;

[0008] The film-forming matrix comprises chitosan and a polymer compound; the polymer compound is corn starch or polyvinyl alcohol.

[0009] Preferably, when the polymer compound is corn starch, the content of prodigiosin in the composite film is 0.5×10 -3 wt%-2×10 -3 wt%.

[0010] Preferably, when the polymer compound is polyvinyl alcohol, the concentration of prodigiosin in the composite film is 0.2 mg / L-1 mg / L.

[0011] Preferably, the fruit is strawberry.

[0012] Preferably, the fruit is banana.

[0013] The present invention provides a method for preparing the above-mentioned composite film, comprising the following steps:

[0014] Mixing the prodigiosin with a film-forming matrix to obtain the composite film;

[0015] The film-forming matrix comprises chitosan and a polymer compound; the polymer compound is corn starch or polyvinyl alcohol.

[0016] Preferably, when the polymer compound is corn starch, the content of prodigiosin in the composite film is 0.5×10 -3 wt%-2×10 -3 wt%.

[0017] Preferably, when the polymer compound is polyvinyl alcohol, the concentration of prodigiosin in the composite film is 0.2 mg / L-1 mg / L.

[0018] The present invention provides application of the composite film in fruit preservation.

[0019] Preferably, the fruit is strawberry or banana.

[0020] The present invention discloses the following technical effects:

[0021] The present invention provides a composite film for fruit preservation, the composite film comprising the following preparation materials: prodigiosin and a film-forming matrix; the film-forming matrix comprising chitosan and a polymer compound; the polymer compound being corn starch or polyvinyl alcohol. Compared with a composite film without prodigiosin, the composite film provided by the present invention can delay the decreasing speed of the weight loss rate, decay rate, titratable acid content and vitamin C content of fruits, can effectively retain the nutrients of fruits, and prolong the storage period of fruits. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 The effect of different concentrations of prodigiosin on the thickness of prodigiosin-chitosan-corn starch composite film;

[0024] Figure 2 The effect of different concentrations of prodigiosin on the water vapor transmission rate of prodigiosin-chitosan-corn starch composite film;

[0025] Figure 3 The effect of different concentrations of prodigiosin on the transmittance of prodigiosin-chitosan-corn starch composite film;

[0026] Figure 4 The effect of prodigiosin-chitosan-corn starch composite film with different concentrations of prodigiosin on the weight loss rate of strawberry;

[0027] Figure 5 The effect of prodigiosin-chitosan-corn starch composite film with different concentrations of prodigiosin on the rot rate of strawberry;

[0028] Figure 6 The effect of prodigiosin-chitosan-corn starch composite films with different prodigiosin concentrations on the titratable acid content of strawberry;

[0029] Figure 7 The effect of prodigiosin-chitosan-corn starch composite films with different concentrations of prodigiosin on the vitamin C content of strawberries;

[0030] Figure 8 This is the result of the inhibition zone of prodigiosin-chitosan-polyvinyl alcohol coating solution;

[0031] Fig. 9 The effect of different concentrations of prodigiosin on the water permeability of prodigiosin-chitosan-polyvinyl alcohol composite membrane;

[0032] Fig.10 The effect of different concentrations of prodigiosin on the oil permeability of prodigiosin-chitosan-polyvinyl alcohol composite membrane;

[0033] Fig.11 The effect of different concentrations of prodigiosin on the opacity of prodigiosin-chitosan-polyvinyl alcohol composite film;

[0034] Fig.12 This is a record of the appearance of banana preservation;

[0035] Fig.13 The effect of prodigiosin-chitosan-polyvinyl alcohol composite film on the weight loss rate of banana;

[0036] Fig.14 The effect of prodigiosin-chitosan-polyvinyl alcohol composite film on the titratable acid content of banana;

[0037] Fig.15 This paper studies the effect of prodigiosin-chitosan-polyvinyl alcohol composite film on the vitamin C content of banana. DETAILED DESCRIPTION

[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0039] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0043] Preparation Example

[0044] The experimental reagents are shown in Table 1, and the experimental instruments are shown in Table 2.

[0045] Table 1 Experimental reagents and manufacturers

[0046] serial number Materials and Reagents Procurement Sources 1 Red Strawberry Commercially available 2 Chitosan (food grade) Qingdao Honghai Biotechnology Co., Ltd. 3 Edible corn starch Xinxiang Liangrun Whole Grain Food Co., Ltd. 4 Prodigiosin Source Leaf Bio 5 2,2'-Hydrazine-bis(3-ethylbenzothiazoline-6-sulfonic acid) diamine salt (ABTS) Shanghai MacLean Biochemical Technology Co., Ltd. 6 2,6-Dichloroindophenol sodium salt hydrate Shanghai MacLean Biochemical Technology Co., Ltd. 7 Phenolphthalein Shanghai MacLean Biochemical Technology Co., Ltd. 8 glycerin Shanghai MacLean Biochemical Technology Co., Ltd. 9 Potassium Persulfate Wenzhou Chemical Materials Factory 10 Sodium hydroxide (analytical grade) Zhejiang Zhongxing Chemical Reagent Co., Ltd. 11 Acetic acid (analytical grade) Jiangsu Qiangsheng Functional Chemicals Co., Ltd. 12 Acetone (analytical grade) Hangzhou Qingchen Chemical Reagent Factory 13 Ethyl acetate (analytical grade) Shanghai Linghan Scientific Instrument Co., Ltd. 14 Dichloromethane (analytical grade) Huzhou Shuanglin Chemical Technology Co., Ltd. 15 Methanol (chromatographic grade) Shanghai MacLean Biochemical Technology Co., Ltd. 16 Petroleum ether (analytical grade) Sinopharm Chemical Reagent Co., Ltd. 17 95% ethanol Huzhou Shuanglin Chemical Technology Co., Ltd. 18 L(+)-Ascorbic Acid Sinopharm Chemical Reagent Co., Ltd. 19 Polyvinyl alcohol Sinopharm Chemical Reagent Co., Ltd.

[0047] Table 2 Experimental instruments and manufacturers

[0048]

[0049]

[0050] Example 1 Preparation of prodigiosin-chitosan-corn starch composite film

[0051] Preparation of prodigiosin-ethanol-glycerol solution: Prodigiosin, ethanol solution and glycerol were mixed in a mass volume ratio of 0.005 g: 5 mL: 0.5 g to obtain prodigiosin-ethanol-glycerol solution;

[0052] 3.0 g corn starch was weighed and dissolved in 100 mL 1% (v / v) acetic acid solution. After magnetic stirring for 30 min in a 90°C water bath, 1.0 g chitosan was added and magnetic stirring was continued for 20 min in a 70°C water bath. After cooling to 25°C, different amounts of prodigiosin-ethanol-glycerol solution were added to obtain prodigiosin with a mass percentage of 0 wt%, 0.5×10 -3 wt%,1×10 -3 wt%、2×10 -3 wt%、4×10 -3 wt% prodigiosin-chitosan-corn starch composite membrane solution;

[0053] 30 mL of the composite film liquid was poured into a sterile plate and placed in a 55°C constant temperature drying oven for 4 h. After drying, the film was peeled off to obtain a prodigiosin-chitosan-corn starch composite film.

[0054] Example 2 Performance measurement of the prodigiosin-chitosan-corn starch composite film prepared in Example 1

[0055] 1. Experimental design

[0056] The performance of the prodigiosin-chitosan-corn starch composite films containing different mass percentages of prodigiosin prepared in Example 1 was tested, mainly including thickness, water vapor permeability, light transmittance and antibacterial ability, and the specific steps were as follows:

[0057] (1) Thickness: Use a vernier caliper with an accuracy of 0.02 mm to randomly select 5 measurement points and take the average value.

[0058] (2) Water vapor transmission rate: Add about 25 mL of deionized water to a 50 mL centrifuge tube, place the membrane on the bottle mouth, and then weigh it. Place the weighed test tube in a constant temperature and humidity dryer, take out the weighing bottle and weigh the mass every 2 hours, measure it continuously for 5 times, and make three parallel measurements for each sample to get the average value. The calculation formula of water vapor transmission rate (WVP) is as follows:

[0059]

[0060] Where: WVP—water vapor transmission coefficient, g·m / (m 2 ·Pa·s); Δm represents the mass loss of the membrane after stabilization, g; x represents the thickness of the composite membrane, m; S represents the area of ​​the membrane that effectively transmits water vapor, m 2 ; Δt represents the time interval between two times after the mass increment is stabilized, s; ​​Δp represents the water vapor pressure difference inside and outside the membrane, that is, the saturated vapor pressure of pure water at 25°C, Δp is 3167Pa.

[0061] (3) Light transmittance: The prodigiosin-chitosan-corn starch composite film was cut into a size suitable for the wells of a 96-well plate, and the prodigiosin-chitosan-corn starch composite film with different prodigiosin concentrations was continuously scanned by an ELISA instrument in the ultraviolet and visible light absorption spectra (280-700nm). Twelve data points were selected to calculate the light transmittance of the prodigiosin-chitosan-corn starch composite film at different wavelengths. The light transmittance calculation formula is as follows:

[0062] T / %=10 -A×100;

[0063] Wherein: A is the absorbance value of prodigiosin-chitosan-corn starch composite film.

[0064] (4) Antibacterial ability: Refer to the method in the literature "Study on the preparation and preservation effect of tea polyphenol-chitosan composite film" (Liang Jie, Zhao Xiaoxu, Liu Tao, et al. Study on the preparation and preservation effect of tea polyphenol-chitosan composite film [J]. Journal of Tropical Crops, 2022, 43(6): 1267-1279.).

[0065] 2. Experimental results

[0066] (1) Effect of prodigiosin addition on the thickness of prodigiosin-chitosan-corn starch composite film Figure 1 As shown. Figure 1 It can be seen that there is no significant difference between the thickness of the prodigiosin-chitosan-corn starch composite film and the concentration of prodigiosin, indicating that the thickness of the prodigiosin-chitosan-corn starch composite film has nothing to do with the amount of prodigiosin added.

[0067] (2) The effect of prodigiosin addition on the water vapor transmission rate (WVP) of prodigiosin-chitosan-corn starch composite film is shown in Figure 2 .Depend on Figure 2 It can be seen that the prodigiosin-chitosan-corn starch composite film with prodigiosin added has a certain barrier ability to water vapor. -3 When the WVP is wt%, it is the lowest. With the increase of prodigiosin concentration, the amount of ethanol added also increases, which will lead to a decrease in the solubility of corn dextrin and an increase in viscosity; the amount of glycerol added also increases, and a small amount of glycerol molecules will be inserted between the macromolecular chains, which increases the density of the prodigiosin-chitosan-corn starch composite film and gradually increases the barrier capacity to water vapor. However, when the amount of ethanol added is too much, it will affect the colloidal structure of dextrin; excessive glycerol will further expand the distance between the original molecular chains; the hydrophobicity of prodigiosin will interact with the chitosan molecules, which will lead to the enlargement of the voids and the increase of holes in the prodigiosin-chitosan-corn starch composite film. The density of the prodigiosin-chitosan-corn starch composite film will also decrease, and water molecules will be easier to move and penetrate. Therefore, when the concentration of prodigiosin exceeds 2×10 - 3 wt%. The WVP of prodigiosin-chitosan-corn starch composite film gradually increased.

[0068] (3) The effect of prodigiosin addition on the light transmittance of prodigiosin-chitosan-corn starch composite film is shown in Figure 3 .Depend on Figure 3It can be seen that within the wavelength range of 380-700nm (visible light), the transmittance of the prodigiosin-chitosan-corn starch composite films with different concentrations of prodigiosin is more than 40%; within the wavelength range of 280-380nm (near ultraviolet), with the increase of prodigiosin concentration, the transmittance of the prodigiosin-chitosan-corn starch composite film continues to decrease, indicating that the prodigiosin-chitosan-corn starch composite film can block ultraviolet rays to a certain extent.

[0069] (4) Escherichia coli and Staphylococcus aureus are common foodborne bacteria. The present invention mainly uses Escherichia coli and Staphylococcus aureus as the test bacteria for the antibacterial activity of prodigiosin-chitosan-corn starch composite film liquid. The inhibitory effect of prodigiosin on Escherichia coli and Staphylococcus aureus is shown in Table 3.

[0070] Table 3 Inhibitory diameters of prodigiosin-chitosan-corn starch composite membranes with different concentrations of prodigiosin against Escherichia coli and Staphylococcus aureus

[0071]

[0072]

[0073] As shown in Table 3, the prodigiosin-chitosan-corn starch composite film liquid has a certain degree of antibacterial effect on Escherichia coli and Staphylococcus aureus. -3 When the concentration of prodigiosin was 0.04477 W / wt%, the inhibition zone was the largest and the antibacterial effect was the strongest. When the concentration of prodigiosin was low, the degree of inhibition increased with the increase of prodigiosin concentration. However, when the concentration of prodigiosin was high, due to the limited diffusion capacity, the size of the inhibition zone no longer increased with the increase of prodigiosin concentration.

[0074] Example 3 Application of the prodigiosin-chitosan-corn starch composite film prepared in Example 1 in strawberry preservation

[0075] 1. Experimental design

[0076] The experiment was conducted by selecting mature red strawberries of uniform size. The experiment was divided into 6 treatment groups, with 5 strawberry samples prepared in each group. The preservation index was measured every 1 day. One group was the control group without treatment, and the other groups were treated with different concentrations of 0wt%, 0.5×10 -3 wt%,1×10 -3 wt%、2×10 -3 wt%、4×10 -3 After the wt% prodigiosin-chitosan-corn starch composite film was wrapped and preserved at room temperature, the selected indicators for determination were weight loss rate, decay rate, titratable acid content and vitamin C content. Three samples were measured in parallel and the average value was taken. The measurement methods of the four indicators are as follows:

[0077] (1) Weight loss rate: measured by weighing method, the weight loss rate calculation formula is as follows:

[0078]

[0079] Where: W0 represents the weight of strawberry on day 0, g; W t Represents the weight after storage, g.

[0080] (2) Decay rate: refer to the method in the literature "Effects of citral on the quality and antioxidant capacity of strawberries during storage" (Tang Xinyue, Cao Yeting, Deng Mingyi, et al. Effects of citral on the quality and antioxidant capacity of strawberries during storage [J]. Journal of Food Safety and Quality, 2024, 15(2): 131-140.).

[0081] (3) Titratable acid content: Take 10g sample homogenate, extract in 80℃ water bath for 30min, cool and adjust the volume to 100mL. Pipette 20mL filtrate into a 250mL conical flask, add 3 drops of phenolphthalein indicator, titrate with 0.1mol / LNaOH, and shake the conical flask while titrating. When the solution changes from colorless to light red and does not fade within half a minute, it is the titration end point. The volume of NaOH consumed at this time is recorded as V', and distilled water is used as a blank control. The titratable acid content calculation formula is as follows:

[0082] Titratable acid content / %=(CNaOH×V′×V) / (m×20);

[0083] Where: V' is the volume of NaOH consumed in titrating the sample solution minus the volume of distilled water used as a blank control; V is the total volume of the test sample, and m is the mass of the strawberry.

[0084] (3) Vitamin C content: The vitamin C content in strawberries was determined by 2,6-dichlorophenol indophenol titration. 10 mL of standard ascorbic acid solution was titrated with 0.1 wt% 2,6-dichlorophenol indophenol until the pink color remained unchanged for 15 s. The mg of ascorbic acid per mL was calculated according to the following formula, which is the titration T.

[0085]

[0086] Where: C is the ascorbic acid concentration (1 mg / mL); V is the ascorbic acid volume (10 mL); V t V is the volume of 0.1% 2,6-dichlorophenol indophenol solution used to titrate 10 mL of ascorbic acid, mL; V2 is the volume of 2,6-dichlorophenol indophenol solution consumed in the titration blank, mL.

[0087] Weigh about 5g of strawberry in a mortar, add 1% oxalic acid and grind into a homogenate, then transfer to a 50mL volumetric flask and dilute with 1wt% oxalic acid, shake well, extract for 12min, and filter. Pipette 10mL of the sample filtrate into a 100mL conical flask and titrate with 0.1wt% 2,6-dichlorophenol indophenol until the pink color remains unchanged for 15s as the end point. At the same time, use 1wt% oxalic acid for blank titration. Each group of samples is operated in parallel 3 times and the average value is taken. The calculation formula is as follows:

[0088]

[0089] Wherein: V1 is the volume of 2,6-dichlorophenol indophenol solution consumed by titrating the sample, mL; V2 is the volume of 2,6-dichlorophenol indophenol solution consumed by titrating the blank, mL; T is the titer, mg / mL; V is the total volume of the extract, mL; W is the sample mass, g; V3 is the volume taken during titration, mL.

[0090] 2. Experimental results

[0091] (1) Effect of prodigiosin-chitosan-corn starch composite film on weight loss rate of strawberry Figure 4 .Depend on Figure 4 It can be seen that with the increase of storage time, the weight loss rate of strawberries in each group showed an increasing trend. The weight loss rate of the control group reached 22.55% after 5 days of storage. -3 The difference between the experimental group and the control group was 10%. In general, the weight loss of strawberries in the prodigiosin-chitosan-corn starch composite film group was less than that in the control group. -3 The results showed that the prodigiosin-chitosan-corn starch composite film group can reduce the water loss of some strawberries. Too low or too high a concentration of prodigiosin will affect the cross-linking degree of the prodigiosin-chitosan-corn starch composite film and cause the water loss of strawberries.

[0092] (2) Effect of prodigiosin-chitosan-corn starch composite film on strawberry decay rate Figure 5 .Depend on Figure 5 It can be seen that the degree of strawberry decay in each group increased with the increase of storage time. The strawberry decay rate in the control group was the highest. -3 wt% experimental group and 2×10 -3 The decay trend of the wt% experimental group was slower; on the 5th day, 1×10 -3 The difference between the experimental group and the control group in wt% was 22.66%. It can be seen that the prodigiosin-chitosan-corn starch composite film with prodigiosin added has a certain antibacterial effect, which is consistent with the results of antibacterial analysis.

[0093] (3) Effect of prodigiosin-chitosan-corn starch composite film on the titratable acid content of strawberry Figure 6 .Depend on Figure 6 It can be seen that the titratable acid content of strawberries in the control group and the groups with different prodigiosin concentrations increased and decreased, which may be related to the difference in the content of strawberries themselves. Overall, compared with the control group, the prodigiosin-chitosan-corn starch composite film with prodigiosin added can slow down the decline of the titratable acid content of strawberries; on the 5th day, 1×10 -3 The difference between the experimental group and the control group was 10% because the prodigiosin-chitosan-corn starch composite film could slow down the respiration of strawberry, thereby reducing the consumption of strawberry titratable acid. The prodigiosin concentration was 1×10 -3 wt% experimental group and 2×10 -3 The wt% experimental group prodigiosin-chitosan-corn starch composite film had a better effect on preserving strawberries.

[0094] (4) Effect of prodigiosin-chitosan-corn starch composite film on vitamin C content of strawberry Figure 7 .Depend on Figure 7 It can be seen that, overall, the VC content of strawberries showed a downward trend. The VC content of strawberries in the control group decreased slightly faster than that in the prodigiosin-chitosan-corn starch composite film group. The prodigiosin concentration was 1×10 -3 wt% experimental group and 2×10 -3 The wt% experimental group of prodigiosin-chitosan-corn starch composite film had a slower decrease in the VC content of strawberry; on the 5th day, 1×10 -3 The difference between the experimental group and the control group was 45.4%. The results showed that the prodigiosin-chitosan-corn starch composite film had the effect of inhibiting the respiration of strawberries. The antioxidant capacity of prodigiosin removed the active oxygen produced by strawberries, thereby inhibiting the oxidase generation pathway and slowing down the oxidation of strawberry VC.

[0095] In summary, chitosan and corn starch were used as raw materials to prepare prodigiosin-chitosan-corn starch composite films, and the thickness, water vapor permeability, light transmittance and other properties were measured. Compared with the composite film without prodigiosin, the performance of the composite film with prodigiosin added was better, and the prodigiosin concentration was 1×10 -3 The effect of wt% is better. Too high or too low prodigiosin concentration will affect the cross-linking degree of prodigiosin-chitosan-corn starch composite film and reduce the performance of the composite film. Based on the preservation of the prepared prodigiosin-chitosan-corn starch composite film, the effect of prodigiosin-chitosan-corn starch composite film with different concentrations of prodigiosin on strawberry preservation was investigated from four physical and chemical indicators: weight loss rate, decay rate, titratable acid content and vitamin C content. The results showed that when the prodigiosin concentration was 1×10 -3 wt% and 2×10-3 The % prodigiosin-chitosan-corn starch composite film reduced the weight loss rate, decay rate, titratable acid content, and vitamin C content of strawberries, and was able to effectively retain the nutrients of strawberries and extend the storage period of strawberries. It can be seen that the prodigiosin-chitosan-corn starch composite film has important application prospects in the preservation of perishable fruits.

[0096] Example 4 Preparation of Prodigiosin-Chitosan-Polyvinyl Alcohol Composite Film

[0097] A certain amount of chitosan is dissolved in a 1.5% acetic acid solution to prepare a 1.5% chitosan solution, and the solution is heated in a water bath at 60°C to obtain a chitosan solution;

[0098] A certain amount of polyvinyl alcohol is dissolved in distilled water, and heated at 90°C until completely dissolved to prepare a 10% polyvinyl alcohol solution, thereby obtaining a polyvinyl alcohol solution;

[0099] Chitosan solution, polyvinyl alcohol solution (maintaining the mass ratio of polyvinyl alcohol to chitosan is 8:2) and prodigiosin solution are uniformly mixed in a certain proportion to prepare prodigiosin-chitosan-polyvinyl alcohol coating solutions with concentrations of 0.2 mg / L, 0.4 mg / L, 0.6 mg / L, 0.8 mg / L and 1.0 mg / L;

[0100] Pour 20 mL of prodigiosin-chitosan-polyvinyl alcohol coating solution into a clean culture dish and let it stand for degassing. After drying at 40°C for 8 hours, peel off the film to obtain a composite film containing prodigiosin-chitosan-polyvinyl alcohol.

[0101] Example 5 Performance measurement of the prodigiosin-chitosan-polyvinyl alcohol composite film prepared in Example 4

[0102] 1. Experimental design

[0103] (1) Inhibition zone test

[0104] The antibacterial effect of prodigiosin-chitosan-polyvinyl alcohol coating solution with different prodigiosin concentrations (0.2mg / L, 0.4mg / L, 0.6mg / L, 0.8mg / L, 1.0mg / L) was determined by the inhibition zone method. Escherichia coli and Staphylococcus aureus were used as the test bacteria, 200μL of bacterial solution was evenly spread on beef extract peptone solid culture medium, and a filter paper with a diameter of 6mm was soaked with prodigiosin-chitosan-polyvinyl alcohol coating solution and placed on the solid culture medium at 37℃ for 24h. The diameter of the inhibition zone was measured with a vernier caliper.

[0105] (2) Water permeability measurement

[0106] According to the method in the literature "Study on the water permeability of modified chitosan fresh-keeping coating" (Ming Li, Shen Dan, Wang Wenping, et al. Study on the water permeability of modified chitosan fresh-keeping coating [J]. Journal of Food and Biotechnology, 2007, 26 (5): 10-13.), 20.00g of anhydrous CaCO3 was placed in a 50mL volumetric bottle, and the prodigiosin-chitosan-polyvinyl alcohol composite film with different prodigiosin concentrations (0.2mg / L, 0.4mg / L, 0.6mg / L, 0.8mg / L, 1.0mg / L) was tightly covered on the bottle mouth, tied with a rubber band and weighed. The volumetric bottle was placed in a closed environment with a relative humidity of 100%; it was weighed again after 24 hours. The water permeability was calculated according to the following formula:

[0107]

[0108] Where: P is the water vapor transmission rate (g·cm 2 ·d -1 );W f is the weight before the experiment (g); W i is the weight after the experiment (g); d is the number of days of static standing; s is the effective area of ​​the prodigiosin-chitosan-polyvinyl alcohol composite film (unit).

[0109] (3) Determination of oil permeability coefficient

[0110] Add 3 mL of peanut oil into a glass bottle, and tightly cover the bottle mouth with prodigiosin-chitosan-polyvinyl alcohol composite films with different prodigiosin concentrations (0.2 mg / L, 0.4 mg / L, 0.6 mg / L, 0.8 mg / L, 1.0 mg / L). Fasten with a rubber band and invert on filter paper. Place in a desiccator for 10 days, weigh the mass of the filter paper before and after, and calculate the oil permeability coefficient of the membrane according to the following formula.

[0111]

[0112] Where: P is the oil permeability coefficient (g·mm / m 2 ·d); ΔW is the difference in filter paper mass before and after (g); FT is the thickness of prodigiosin-chitosan-polyvinyl alcohol composite film (mm); s is the effective area of ​​prodigiosin-chitosan-polyvinyl alcohol composite film (m 2 ); T is the placement time (d).

[0113] (4) Determination of light opacity

[0114] The prodigiosin-chitosan-polyvinyl alcohol composite films with different prodigiosin concentrations (0.2 mg / L, 0.4 mg / L, 0.6 mg / L, 0.8 mg / L, 1.0 mg / L) were cut into a size of 10 mm × 30 mm and covered on one side of the cuvette. The cuvette not covered with the prodigiosin-chitosan-polyvinyl alcohol composite film was used as a reference, and the absorbance of the plastic wrap was measured at 460 nm.

[0115]

[0116] Where: B is the opacity of prodigiosin-chitosan-polyvinyl alcohol composite film; Abs 460 is the absorbance of prodigiosin-chitosan-polyvinyl alcohol composite film at 460nm; d is the thickness of prodigiosin-chitosan-polyvinyl alcohol composite film (mm).

[0117] 2. Experimental results

[0118] (1) Escherichia coli and Staphylococcus aureus are both common spoilage bacteria. The inhibition zone results are as follows Figure 8 As shown. The results of the inhibition zone show that the prodigiosin-chitosan-polyvinyl alcohol coating liquid has the ability to inhibit both Escherichia coli and Staphylococcus aureus, and the antibacterial effect is better with the increase of the concentration of prodigiosin. The same concentration of prodigiosin-chitosan-polyvinyl alcohol coating liquid has a better antibacterial effect on Staphylococcus aureus than Escherichia coli. In this experiment, the diameter of the inhibition zone of the prodigiosin-chitosan-polyvinyl alcohol coating liquid formed by the prodigiosin with a concentration of 1.0 mg / L is the largest, reaching 11.02 mm for Escherichia coli and 11.65 mm for Staphylococcus aureus. The prodigiosin-chitosan-polyvinyl alcohol coating liquid formed by the prodigiosin with a concentration of 0.2 mg / L has the smallest diameter of the inhibition zone in all experimental groups, reaching 7.55 mm for Escherichia coli and 8.71 mm for Staphylococcus aureus.

[0119] (2) Effects of different concentrations of prodigiosin on the water permeability of prodigiosin-chitosan-polyvinyl alcohol composite membranes Fig. 9 The results show that the higher the concentration of prodigiosin, the lower the water permeability of the composite membrane. When the amount of prodigiosin added is 0.2 mg / L, the water permeability is the highest, which is 0.1323 g·cm 2 ·d -1 When the amount of prodigiosin added was 1.0 mg / L, the water permeability was the smallest, which was 0.1121 g·cm 2 ·d -1 .

[0120] (3) Effects of different concentrations of prodigiosin on the oil permeability of prodigiosin-chitosan-polyvinyl alcohol composite membranes Fig.10The results showed that there was no significant difference in the overall oil resistance coefficient (p<0.05), and the oil resistance coefficient was lower than 0.10g·mm / m 2 ·d. The coating has strong oil resistance.

[0121] (4) Effects of different concentrations of prodigiosin on the light transmittance of prodigiosin-chitosan-polyvinyl alcohol composite films Fig.11 As shown. Fig.11 It can be seen that the light opacity of the prodigiosin-chitosan-polyvinyl alcohol composite film is greatly affected by the concentration of prodigiosin, and the light opacity increases significantly with the increase of the concentration of prodigiosin.

[0122] Example 6 Application of the prodigiosin-chitosan-polyvinyl alcohol composite film prepared in Example 4 in banana preservation

[0123] Based on the research results of antibacterial and some physical properties of prodigiosin-chitosan-polyvinyl alcohol composite films with different prodigiosin concentrations, the composite coating with prodigiosin concentration of 1 mg / L was selected for banana preservation experiment.

[0124] 1. Experimental design

[0125] Bananas of uniform size and moderate maturity were selected and stored at room temperature after treatment. The experiment was divided into the following groups: blank group, PE film wrapped group (commercially available, control group), prodigiosin-chitosan-polyvinyl alcohol composite film group (also known as prodigiosin composite coating group or experimental group). Each group was stored at room temperature after treatment, and 3 parallel samples were randomly sampled from each group each time, and the test was conducted once every 2 days. The specific test indicators are as follows:

[0126] (1) Appearance evaluation

[0127] During the storage process, each group of banana samples was photographed and recorded every 2 days to observe the freshness, color changes and degree of decay of the samples.

[0128] (2) Weight loss rate

[0129] Weigh the bananas and calculate the banana weight loss rate according to the following formula.

[0130]

[0131] Where: m0 is the weight of bananas before storage; m t To save the weight on day t.

[0132] (3) Titratable acid

[0133] Take 10g of banana homogenate, add 20mL of deionized water, mix well, and filter through four layers of gauze. Take 5mL of supernatant and add 50μL of phenolphthalein indicator, titrate with 0.1mol / LNaOH solution until the solution turns pink and does not fade for 30s, and record the volume consumed. The formula for calculating vitamin C content is as follows:

[0134]

[0135] Wherein: C is the concentration of NaOH solution (0.1 mol / L); V is the volume of NaOH solution consumed (mL); V1 is the volume of the titrated supernatant (mL); V2 is the total volume of the supernatant (mL); W is the fresh weight of banana used (g).

[0136] (4) Vitamin C content

[0137] The content of vitamin C was determined by 2,6-dichlorophenol indophenol titration. Take 10g of banana homogenate, add 20mL of 1wt% oxalic acid solution, mix well, and filter through four layers of gauze. Titrate 10mL of supernatant with 0.1% 2,6-dichlorophenol indophenol solution until it turns light red and does not fade for 30s. The consumed volume is recorded as V1. Titrate 10mL of 1% oxalic acid solution again, and the consumed volume is recorded as V2. Finally, titrate 10mL of standard ascorbic acid solution, and the consumed volume is recorded as V T . Calculate the titer T according to the following formula.

[0138]

[0139] Where: T is the titer (mg / mL); V and C are the volume and concentration of ascorbic acid (mL, mg / mL), respectively; V T V2 is the volume (mL) of 2,6-dichlorophenol indophenol consumed in the titration of ascorbic acid; V3 is the volume (mL) of 2,6-dichlorophenol indophenol consumed in the titration of oxalic acid.

[0140] The vitamin content was calculated according to the following formula.

[0141]

[0142] Wherein: T is the titration degree of the titrant (mg / mL); V is the total volume of banana supernatant (mL); W is the fresh weight of banana used (g); V1 is the volume of 2,6-dichlorophenol indophenol consumed in the titration sample (mL); V2 is the volume of 2,6-dichlorophenol indophenol sodium consumed in the titration blank (mL); V3 is the volume of the titrated sample (mL).

[0143] 2. Experimental results

[0144] (1) Freshness, color change and decay degree of bananas in different treatment groups Fig.12 As shown. Fig.12 It can be seen that as the storage time increases, a large number of black spots appear on the fourth day in the blank group without treatment, large black spots appear on the sixth day in the control group, and large black spots appear on the eighth day in the experimental group. It can be seen that the prodigiosin-chitosan-polyvinyl alcohol composite film has a significant effect on the preservation of bananas.

[0145] (2) During the storage process of bananas, due to respiration and transpiration, the nutrients of bananas are consumed and the weight decreases. The effects of different treatments on the weight loss rate of bananas are shown in Fig.13 .Depend on Fig.13 It can be seen that as the storage time increases, the weight loss rate of bananas increases. On the tenth day of storage, the weight loss rate of the untreated group reached 12.7%, while that of the PE film group and the prodigiosin composite coating group was 5.26% and 4.34%, respectively. The weight loss rate of the untreated blank group was significantly higher than that of the PE film treatment group and the prodigiosin composite coating group (p<0.05).

[0146] (3) Effects of different treatments on the titratable acidity of bananas. Fig.14 .Depend on Fig.14 It can be seen that the titratable acid content of bananas decreases with the extension of storage time. On the tenth day of storage, the titratable acid content of the blank group without treatment decreased from 2.68mmol / 100g to 1.79mmol / 100g, and the titratable acid content of the PE film group and the prodigiosin composite coating group decreased to 1.98mmol / 100g and 2.04mmol / 100g, respectively. The titratable acid content of the untreated group was significantly higher than that of the PE film group and the prodigiosin composite coating group (p<0.05).

[0147] (4) The vitamin C content in fruits can indirectly reflect the maturity of fruits. As the fruits develop, the vitamin C content decreases. The effects of different treatments on the vitamin C content of bananas are shown in Fig.15 .Depend on Fig.15 It can be seen that the vitamin C content of bananas decreases with the extension of storage time. On the tenth day of storage, the vitamin C content of the blank group without treatment decreased from 3.211 mg / 100g to 2.119 mg / 100g, and the PE film group and the prodigiosin composite coating group decreased to 2.539 mg / 100g and 2.631 mg / 100g respectively. The titratable acid content of the untreated group was significantly higher than that of the PE film group and the prodigiosin composite coating treatment group (p<0.05). The experimental results show that the prodigiosin composite coating can effectively delay the decline of vitamin C content to a certain extent.

[0148] In summary, in the performance research experiment of prodigiosin-chitosan-polyvinyl alcohol composite membrane, the antibacterial property, water permeability, oil permeability coefficient and light opacity of the prodigiosin-chitosan-polyvinyl alcohol composite membrane were measured. The study showed that in this experiment, when the addition amount of prodigiosin was as low as 0.2 mg / L, the diameter of the inhibition zone of the prodigiosin-chitosan-polyvinyl alcohol composite membrane was also the smallest, with an inhibition zone diameter of 7.55 mm for Escherichia coli and 8.71 mm for Staphylococcus aureus; the water permeability was the highest at 0.1323 g·cm 2 / d; the maximum oil permeability coefficient is 0.0960g·mm / m 2 ·d. The minimum opacity is 18.9%. When the maximum amount of prodigiosin added is 1.0 mg / L, the diameter of the inhibition zone is the largest, the diameter of the inhibition zone for Escherichia coli is 11.02 mm, and the antibacterial effect on Staphylococcus aureus is 11.65 mm. The minimum water permeability is 0.1121 g·cm 2 / d; the minimum oil permeability coefficient is 0.0930g·mm / m 2 d; the highest opacity is 47.7%. Through the analysis of the experimental results of the study on the performance of prodigiosin-chitosan / polyvinyl alcohol composite film, the prodigiosin-chitosan-polyvinyl alcohol composite film with a prodigiosin concentration of 1.0 mg / L was finally selected for banana preservation. Through the apparent record and the determination of weight loss rate, titratable acid and vitamin C content, the results showed that the composite film effectively delayed the decay of bananas, reduced the weight loss rate and the loss of nutrients such as titratable acid and vitamin C, so the prodigiosin-chitosan-polyvinyl alcohol composite film can effectively extend the shelf life of bananas.

[0149] Studies have shown that prodigiosin is actually non-toxic, so prodigiosin can be used for food preservation. At the same time, since chitosan and polyvinyl alcohol are edible and degradable, they will not harm human health and the environment. The present invention confirms the feasibility and effectiveness of prodigiosin-chitosan-polyvinyl alcohol composite film for banana preservation, and provides a new preservation method for other fruits and foods, which has broad application prospects.

[0150] The embodiments described above are only descriptions of the preferred embodiments of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A composite film for preserving fruits, characterized in that: The composite film comprises the following preparation raw materials: prodigiosin and a film-forming matrix; The film-forming matrix comprises chitosan and a polymer compound; the polymer compound is corn starch or polyvinyl alcohol.

2. The composite membrane according to claim 1, characterized in that When the polymer compound is corn starch, the content of prodigiosin in the composite film is 0.5×10 -3 wt%-2×10 -3 wt%.

3. The composite membrane according to claim 1, characterized in that When the polymer compound is polyvinyl alcohol, the concentration of prodigiosin in the composite film is 0.2 mg / L-1 mg / L.

4. The composite membrane according to claim 2, characterized in that The fruit is strawberry.

5. The composite membrane according to claim 3, characterized in that The fruit is banana.

6. The method for preparing the composite film according to claim 1, characterized in that: The following steps are involved: Mixing the prodigiosin with a film-forming matrix to obtain the composite film; The film-forming matrix comprises chitosan and a polymer compound; the polymer compound is corn starch or polyvinyl alcohol.

7. The preparation method according to claim 6, characterized in that: When the polymer compound is corn starch, the content of prodigiosin in the composite film is 0.5×10 -3 wt%-2×10 -3 wt%.

8. The preparation method according to claim 6, characterized in that: When the polymer compound is polyvinyl alcohol, the concentration of prodigiosin in the composite film is 0.2 mg / L-1 mg / L.

9. Use of the composite film according to any one of claims 1 to 5 in preserving fruits.

10. The use according to claim 9, characterized in that: The fruits are strawberries, bananas and other fruits.

Citation Information

Cited By

  • Application of prodigiosin in promoting germination of plant seeds

    CN120240064A

  • Incense-burning oxygen-consuming carbon dioxide-supplementing food preservation bag for household refrigerator

    CN224455047U